PERSPEKTIF HUKUM DAN KEADILAN TERHADAP KASUS BUAH RANDU DI KABUPATEN BATANG - Waidin Waidin (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Human needs society to socialize and to maintain the orderliness in the society required norms as guidelines. One of these norms is legal norm that not only written law but also an unwritten law such as customary law and customs of society. The main purpose of law is justice, because it can maintain relationship with the community. Therefore, law enforcement officer carrying out their duties to make justice, not merely apply the law texts for the sake of legal certainty. In the case of cotton fruits, judges prefer to the certainty of the law rather than justice. The judge did not consider the habits of the local community, that’s why the perpetrator felt unfairly treated. To create justice in the society, judges should not only guide by the law text but must also consider the habits of the local community.Keyword: Law, justice and legal certainty